Impact of phytochemical-based hydrocolloid dressings on wound healing: A comparative review - Sipho Sibanda; Mapula Razwinani; Keolebogile Shirley Motaung (Journal of Medicinal Plants for Economic Development)
Background: Wound healing is an important occurrence consisting of a myriad biochemical processes. The recent introduction of phytochemical-based dressings to expedite wound healing uses a multi-targeted approach including antimicrobial, anti-inflammatory and antioxidant activity.